1989
DOI: 10.1039/p19890001841
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diels–Alder reactions. Part 3. Influence of butadiene structure upon the diastereofacial reactivity of (E)-1-(2′,3′,4′,6′-tetra-O-acetyl-β-D-glucopyranosyloxy)buta-1,3-dienes

Abstract: A460 7 0 D (E) -1 -(2',3',4',6'-Tetra-~-acetyl-~-~-glucopyranosyloxy) buta-l,3-diene ( I c), its 3-methyl derivative (1 d), its 2,3-dimethyl derivative (1 e), its (32) -4-acetoxy-3-(t-butyldimethylsilyloxy) derivative ( I f ) , its 3 -(t-butyldimethylsilyloxy) derivative (1 g), and its (32) -3-(t-butyldimethylsilyloxy) -2,4-dimethyl derivative (1 h) have been prepared and their diastereofacial reactivities towards N-phenylmaleimide and tetracyanoethylene assessed. With the former dienophile in benzene at ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 5 publications
(6 reference statements)
1
28
0
Order By: Relevance
“…12 ( 3 6.90 [a] 0.32 [a] 22 ____ [c,d] 14.7 [b] 67.4 [c] 0.23 ____ [c,d] 25.2 [b] 90.0 [c] 0.42 O-acetyl-α-D-glucopyranosyl bromide (ABG) was prepared according lit. 16 , potassium 3hydroxypropenal 17 was combined to ABG 18 followed by addition of tributylphosphorane. 9 The diene obtained was subjected to 4-phenyl-1,2,4-triazole-3,5-dione (PTAD) to obtain the adduct 10.…”
Section: -N-phenyl Carboxamide Derivatives Of 1-azafagomine: New Leamentioning
confidence: 99%
“…12 ( 3 6.90 [a] 0.32 [a] 22 ____ [c,d] 14.7 [b] 67.4 [c] 0.23 ____ [c,d] 25.2 [b] 90.0 [c] 0.42 O-acetyl-α-D-glucopyranosyl bromide (ABG) was prepared according lit. 16 , potassium 3hydroxypropenal 17 was combined to ABG 18 followed by addition of tributylphosphorane. 9 The diene obtained was subjected to 4-phenyl-1,2,4-triazole-3,5-dione (PTAD) to obtain the adduct 10.…”
Section: -N-phenyl Carboxamide Derivatives Of 1-azafagomine: New Leamentioning
confidence: 99%
“…The chemical synthesis of two BABS derivatives started from conveniently prepared D-GlcNAc derivative 39 (Scheme 7). 60 Firstly, a regio-and stereoselective bromoalkoxylation of 39 was completed using N-bromosuccinimide (NBS) and 2-(2-azidoethoxy)ethanol followed by a three-step one-pot functional group manipulation to deliver carboxylic acid 40. An EDANS donor fluorophore was then installed using amide coupling with carboxylate 40 followed by addition of a DABCYL quencher through the pendant azide.…”
Section: Reviewmentioning
confidence: 99%
“…[98][99][100] The authors had previously demonstrated that 1-oxybuta-1,3-dienes with a 2,3,4,6-tetra-O-acetyl-b-D -glucopyranosyl chiral auxiliary are efficient to induce a good level of diastereoselectivity in Diels-Alder cycloadditions. The dienyl methyl ester 210a and benzyl ester 210b were selected to study their reactivity toward azo compounds.…”
Section: Azo Dienophilesmentioning
confidence: 99%